Antibody levels by indirect ELISA test in Trypanosoma evansi infected horses following treatment with quinapyramine sulphate - Monzon, Carlos Manuel (2003)
An ELISA test was used to determine the persistence of antibody levels in horses following treatment for Trypanosoma evansi. In 17 horses with T. evansi from two farms treated and cured with quinapyramine sulphate, ELISA antibody levels fell progressively post-treatment, but remained with positive results for 22.6 months in one horse, 12.8 months in a second, 4.1 months in another four and 2.3 months in three, whilst the rest became negative at 2.3 months. In two horses that suffered a post-treatment infection relapse the decrease in ELISA levels was only temporary, and a new increase in antibody levels was proven. The follow-up of these antibody levels could prove useful in clinical cases and in epidemiological studies, as well as for assessing the efficacy of drug treatment